Sonographic Assessment of Submandibular Salivary Glands in Hypothyroid Rat's Pups Before and After Ashwagandha Root Extract Treatment - Zahraa Alhalawachee; Ghada Abd Alrhman Taqa (University of Mosul, 2023)
Background: One of the most common chronic diseases globally is hypothyroidism. Thyroid hormones serve a significant role in maintaining the proper function and shape of the salivary gland. The aim of the study: Investigate the function of Ashwagandha roots extract in providing a protection role for salivary glands in hypothyroid rats following postnatal exposure to Propylthiouracil. Materials and Methods: Ten pregnant albino rats were obtained. Until the rat pups were detected, each pregnant rat was kept individually in clean rodent plastic. At postnatal day 3 (PND3), forty male rats were randomly assigned to one of two groups: group A, which served as a control group, and group B, which received orally (1mg/kg) Propylthiouracil (PTU) for three weeks. At PND22, group B was divided up into three subgroups: B1, the hypothyroid group that got no therapy; B2, the hypothyroid group that received an aqueous extract of Ashwagandha roots (200 mg/kg) for 21 days; and B3, the hypothyroid group that received Levothyroxine (4g/100g/day) for 21 days. At the end of the trial, the submandibular gland was assessed using sonographic instruments in all groups. Results: the sonographic assessment of hypothyroid group’s submandibular gland showed an increase in the overall size of the gland, a heterogeneous gland with a honeycomb appearance and hypoechoic regions in group remains without treatment, while the results in hypothyroid pups fed with Ashwagandha roots extract indicated a small improvement in gland size and echotexture when compared to pups who received levothyroxine, owing to its antioxidant properties.